CHALLENGES FACED BY UZBEK STUDENTS IN LEARNING ENGLISH AS A SECOND LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study investigates the challenges encountered by Uzbek students in learning English as a second language (ESL). Despite various educational reforms aimed at improving English proficiency, many students still face significant difficulties, including linguistic barriers, psychological challenges, and limitations within the institutional framework. This research uses a mixed-methods approach, combining surveys and semi-structured interviews with undergraduate students from Tashkent universities to understand the primary obstacles to ESL learning. The findings highlight issues such as grammar and vocabulary limitations, anxiety, low motivation, and the lack of real-life language exposure. Recommendations are provided for both educators and students to enhance the learning process, emphasizing more communicative teaching strategies, increased use of digital tools, and practical language practice.